1994
DOI: 10.1002/ajim.4700250404
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer mortality and airways obstruction among metal miners exposed to silica and low levels of radon daughters

Abstract: Starting from a cross-sectional survey in 1973, the mortality of two cohorts of Sardinian metal miners was followed through December 31, 1988. In mine A, the quartz concentration in respirable dust ranged between 0.2% and 2.0% and the exposure to radon daughters averaged 0.13 working level (WL), with the highest estimated cumulative exposure around 80-120 WLM. In mine B, the silica content was much higher (6.5-29%), but exposure to radon daughters was significantly lower than in mine A. More than 98% of the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
6
16
1
Order By: Relevance
“…This was true even after tobacco exposure and other covariates were controlled for. This finding is consistent with those in the literature, suggesting that a greater degree of airway obstruction (decreased FEV 1 /FVC) is associated with an increased risk of lung cancer (30)(31)(32), even after adjustment for smoking.…”
Section: Discussionsupporting
confidence: 92%
“…This was true even after tobacco exposure and other covariates were controlled for. This finding is consistent with those in the literature, suggesting that a greater degree of airway obstruction (decreased FEV 1 /FVC) is associated with an increased risk of lung cancer (30)(31)(32), even after adjustment for smoking.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of p53 expression in dysplasias without pneumoconiosis was very low in bronchioli, particularly in cases without lung cancer, in contrast to pneumoconiotic cases where frequent p53 expression was sustained in bronchiolar dysplasias from patients without lung cancer. These findings support epidemiological results showing a positive causal relationship between pneumoconiosis and lung cancer (Chiyotani et al, 1990;Checkoway et al, 1993;Wang et al, 1996; , 1997) and are in contrast to reports of a negative causal relationship (Meijers et al, 1990;Carta et al, 1994;Starzynski et al, 1996). We cannot specify the reasons behind our observations but speculate that certain genetic damages peculiar to pneumoconiosis might be induced frequently and preferentially in bronchiolar peripheral epithelia.…”
Section: Discussionsupporting
confidence: 76%
“…Pneumoconiosis and occupational exposure to silica have long been implicated in the pathogenesis of lung cancer (Chiyotani et al, 1990;Checkoway et al, 1993;Wang et al, 1996;Hnizdo et al, 1997), while some studies failed to find excess incidence of lung cancer with pneumoconiosis (Meijers et al, 1990;Carta et al, 1994;Starzynski et al, 1996). In addition to epidemiological studies, some in vitro and in vivo studies have demonstrated that silica per se can be carcinogenic in rats, though these data may not be applied directly to human cancers due to species-related differences in carcinogenesis (Saffioti, 1992).…”
mentioning
confidence: 99%
“…14 From about 2000 workers investigated in our Institute in Sardinia, Italy for awarding compensation, the cohort included 724 silicotic patients who had a radiographically confirmed diagnosis between 1964 and 1970. The original chest x ray films, reviewed by two independent blinded readers, were classified according to the ILO 12 point classification scale of profusion,15 assigning a midpoint category when a disagreement between readers was present.…”
Section: Methodsmentioning
confidence: 99%